DETERMINAN AKUNTABILITAS KINERJA INSTANSI PEMERINTAH : STUDI PADA PEMERINTAH KOTA PEKANBARU - Sri Hayani; Julita Julita (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2021)
The study aimed to determine :the influence of budget goal clarity, government official competence, internal control, and obedience to the laws and regulations on the performance accountability of government agencies.The population in this study is 43 OPD’s Pekanbaru City. In this study, the sample used was 32 OPD with a total 96 respondents using purposive sampling method. This study uses primary data by distribusing questionnaires. The analytical method used in this study is multiple linear regression analysis. The analycal tool used in this study is software SPSS version 25.0. The results of this study indicate datebudget goal clarity influences on the performance accountability of government agencies, government official competence influences on the performance accountability of government agencies,internal control influences on the performance accountability of government agencies, obedience to the laws and regulationsinfluenceson the performanceaccountability of government agencies.